2014
DOI: 10.5424/sjar/2014121-4662
|View full text |Cite
|
Sign up to set email alerts
|

Effect of olive mill wastewater on growth and bulb production of tulip plants infected by bulb diseases

Abstract: The effect of olive mill wastewater (OMW) on growth of tulip plants infected by common diseases as well as on their new bulbs production is analyzed in this work. Filtered and sterilized OMW was tested as growth inhibitor of Botrytis tulipae, Fusarium oxysporum, Aspergillus niger and Penicillium spp. mycelium. The effect of filtered OMW on uninfected tulip bulbs was also tested as well as on the growth of bulbs infected with the fungus B. tulipae and A. niger in vivo. The mycelium length, severity of scab-like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Furthermore, studies on the use of OMWW has been demonstrated that it can act as phytoprotective compound on fruits and vegetables during the growing season and after harvest during storage offering a promising solution for preventing losses of fruits and vegetables from post-harvest attacks such as those from the fungus B. cinerea [69,73]. Similar results have been reported by other studies [65,[91][92][93] where the use of OMWW can affect the growth of saprophytic fungi, the incidence of foliar diseases, and the growth of soil-borne pathogens before and after harvest in strawberries and in tulip plants. Furthermore, in another study has been reported that substances extracted from OMWW showing antifungal action inhibited the mycelium growth of Fusarium solani and R. solani [94].…”
Section: Discussionsupporting
confidence: 77%
“…Furthermore, studies on the use of OMWW has been demonstrated that it can act as phytoprotective compound on fruits and vegetables during the growing season and after harvest during storage offering a promising solution for preventing losses of fruits and vegetables from post-harvest attacks such as those from the fungus B. cinerea [69,73]. Similar results have been reported by other studies [65,[91][92][93] where the use of OMWW can affect the growth of saprophytic fungi, the incidence of foliar diseases, and the growth of soil-borne pathogens before and after harvest in strawberries and in tulip plants. Furthermore, in another study has been reported that substances extracted from OMWW showing antifungal action inhibited the mycelium growth of Fusarium solani and R. solani [94].…”
Section: Discussionsupporting
confidence: 77%
“…Regarding the use of OMWW, it is well known that OMWW are the main pollutant parameter responsible for the severe environmental impact of wastewater mills especially in the Mediterranean countries. However, several research studies have demonstrated the potential use of these compounds as environmental friendly plant protective method applied on several plant species producing fruits, vegetables and flowers during the growing season and postharvest period under storage conditions [68][69][70][71]. Furthermore, Kotsou et al, [72] reported that OMWW shown antifungal action against R. solani in field experiments while Mavrakis,[73] also reported that various forms of OMWW polyphenols and especially the liquid one affect the development of several important plant pathogenic fungi such as B. cinerea, A. alternata, F. oxysporum f.sp., melonis, Rhizopus species, C. higginsianum, and P. parasitica var.…”
Section: Discussionmentioning
confidence: 99%
“…The strong fungicidal activity of water extracts of WPO, diluted 1:10, was demonstrated against Phytophthora capsica [139]. The filter sterilized OMWW also inhibited the in vitro mycelium growth of B. tulipae, F. oxysporum, Aspergillus niger, and Penicillium spp [140].…”
Section: Effects Of Omw As Biopesticides In Plant Protectionmentioning
confidence: 95%